To add 2√8 + 3√8, we first recognize that both terms have the same radicand of 8. Therefore, we can combine them by adding the coefficients:
2√8 + 3√8 = (2 + 3)√8 = 5√8
So, the sum of 2√8 and 3√8 is 5√8.
Add 2√8 + 3√8.(1 point)
7 answers
add √31 + √31
To add √31 + √31, we simply combine the like terms:
√31 + √31 = 2√31
So, the sum of √31 and √31 is 2√31.
√31 + √31 = 2√31
So, the sum of √31 and √31 is 2√31.
subtract 7√5 - 4 √5
To subtract 7√5 - 4√5, we simply combine the like terms:
7√5 - 4√5 = (7 - 4)√5 = 3√5
So, the difference between 7√5 and 4√5 is 3√5.
7√5 - 4√5 = (7 - 4)√5 = 3√5
So, the difference between 7√5 and 4√5 is 3√5.
subtract √29 - √29
To subtract √29 - √29, we can simplify the expression by combining the like terms:
√29 - √29 = 0
So, the difference between √29 and √29 is 0.
√29 - √29 = 0
So, the difference between √29 and √29 is 0.